Hippocampal synaptic plasticity, spatial memory and anxiety - Bannerman, David; Sprengel, Rolf; Sanderson, David; McHugh, Stephen B.; Rawlins, J. Nicholas P.; Monyer, Hannah; Seeburg, Peter H. (Nature reviews. Neuroscience, 2014)
In this Perspective, Seeburg and colleagues re-examine the role of the hippocampus in spatial learning in light of recent findings. They also suggest that the hippocampus has a role in resolving conflict or uncertainty that might also explain its role in anxiety.